Do engineer perceptions about automated vehicles match user trust? Consequences for design. (November 2020) - Walker, F.; Steinke, J.; Martens, M.H.; Verwey, W.B.
Highlights: User trust and engineer evaluations of vehicle reliability are often misaligned. The degree of alignment differs between driving situations. Modifications to vehicle dynamics and HMI may improve trust calibration. First-time users prefer lower driving speeds and smoother trajectory corrections. Visual representations of objects detected could improve trust calibration. Real-time feedback on vehicle performance may improve trust calibration. Abstract: To maximize road safety, driver trust in an automated vehicle should be aligned with the vehicle's technical reliability, avoiding under- and over-estimation of its capabilities. This is known as trust calibration. In the study reported here, we asked how far participant assessments of vehicle capabilities aligned with those of the engineers. This was done by asking the engineers to rate the reliability of the vehicle in a specific set of scenarios. We then carried out a driving simulator study using the same scenarios, and measured participant trust. The results suggest that user trust and engineer perceptions of vehicle reliability are often misaligned, with users sometimes under-trusting and sometimes over-trusting vehicle capabilities. On these bases, we formulated recommendations to mitigate under- and over-trust. Specific recommendations to improve trust calibration include the adoption of a more defensive driving style for first-time users, the visual representation of the objects detected by the automated driving system in its surroundings in the Human Machine Interface, and real-time feedback on the performance of the technology.